Development of Korean Pavement Design Guide for Asphalt Pavements Based on the Mechanistic-Empirical Design Principle - Anh Thang Le; Hyun Jong Lee; Hee Mun Park; Tae Woo Kim (The Baltic Journal of Road and Bridge Engineering)
Recently, the Korean Pavement Design Guide (KPDG) has been developed based on the mechanistic-empirical design principle as part of the Korea Pavement Research Program (KPRP). This paper presents the detailed information about the input parameters and pavement performance models used in the KPDG for new construction of asphalt pavements. Input parameters for pavement design such as traffic, environment, and materials were characterized by considering the domestic condition. The structural analysis program based on the layer elastic theory has been developed to calculate the critical pavement responses in asphalt pavements. The pavement performance models for fatigue cracking and rutting were developed and calibrated using various types of laboratory testing results and field monitoring data. The procedure for determining the critical evaluation points in calculating the pavement responses has been proposed to reduce the computational time of the design program. The concept of stiffness reduction of asphalt mixtures was also incorporated with the structural analysis program and pavement performance models for more realistic prediction of the pavement distresses.